2009
DOI: 10.1002/stem.206
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Spermatogonial Stem Cell Subsets by Morphological Analysis and Prospective Isolation

Abstract: Spermatogenesis is maintained by a pool of spermatogonial stem cells (SSCs). Analyses of the molecular profile of SSCs have revealed the existence of subsets, indicating that the stem cell population is more heterogeneous than previously believed. However, SSC subsets are poorly characterized. In rodents, the first steps in spermatogenesis have been extensively investigated, both under physiological conditions and during the regenerative phase that follows germ cell damage. In the widely accepted model, the SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 34 publications
(54 reference statements)
13
100
1
Order By: Relevance
“…The analysis of clone distribution revealed that while the numbers of clones of 1 and 2 GFRA1C spermatogonia remain constant in all stages, clones of 4 and 8 GFRA1C spermatogonia are differentially distributed with a significant decrease of GFRA1C Aal4 in stages VII-VIII and relatively large numbers of GFRA1C Aal4 and Aal8 clones in stages IX-XI. This further supports the concept of heterogeneity of gene expression among undifferentiated spermatogonia during the epithelial cycle (Grisanti et al 2009, Nakagawa et al 2010.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The analysis of clone distribution revealed that while the numbers of clones of 1 and 2 GFRA1C spermatogonia remain constant in all stages, clones of 4 and 8 GFRA1C spermatogonia are differentially distributed with a significant decrease of GFRA1C Aal4 in stages VII-VIII and relatively large numbers of GFRA1C Aal4 and Aal8 clones in stages IX-XI. This further supports the concept of heterogeneity of gene expression among undifferentiated spermatogonia during the epithelial cycle (Grisanti et al 2009, Nakagawa et al 2010.…”
Section: Discussionsupporting
confidence: 83%
“…The total number of ZBTB16C spermatogonia, including type As, Apr and Aal spermatogonia, their corresponding GFRA1 staining status and Sertoli cell nuclei were counted within the grid on randomly selected tubules. A ZBTB16C cell was described as type As if surrounding cells within 25 mm lacked ZBTB16 staining and exhibited a dissimilar nuclear morphology; furthermore, doublets of cells were designated type Apr when the internuclear distance was below 25 mm (Tegelenbosch & de Rooij 1993, Grisanti et al 2009 …”
Section: Whole-mount Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13] In cotransplanted with allogeneic cells, Sertoli cells not only are immune privileged, but also assist fibromyoblasts and islet cells in escaping immune rejection, which allows the long-term survival of the grafts. [14][15][16][17][18][19] Such privilege is thought to be associated with the FasL expressed on the surface of Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
“…In undifferentiated spermatogonia, transplantable stem cell activity was detected both in Gfra1 pos and in Gfra1 neg (likely to be Neurog3 pos ) fractions (Hofmann et al 2005a, Nakagawa et al 2007, Grisanti et al 2009). It is noteworthy that in vitro culture that retains the stem cell activity, another big breakthrough in this field, has been developed taking advantage of this transplantationbased stem cell assay (Kanatsu- Shinohara et al 2003, Kubota et al 2004.…”
Section: Spermatogenic Stem Cell Modelsmentioning
confidence: 99%